Necrotizing fasciitis: a tertiary centre based study - Ekka, Nishith M. Paul; Kujur, Archana Dipa Sangita; Mishra, Gaurav (International Surgery Journal, 2018)
Background: Necrotizing fasciitis is a limb or life-threatening, invasive soft-tissue infection, although known since ancient times was first described in 1871. The purpose of the present study is to analyze the clinical presentation, bacterial flora, predisposing and co-morbid conditions, surgical and resuscitative treatment and outcome of this soft tissue infection. Methods: This is a prospective, cross-sectional, clinical study which was conducted from May 2016 until April 2018. This study included 60 consecutive patients. Age, gender, clinical presentation, co-morbid conditions and predisposing factors and pus culture sensitivity, treatment given, and its outcome were recorded. Results: With a male female ratio of 2.33:1 and median age of 46, most involves site was lower limb. Most patients presented with history of trauma followed by swelling (100%), pain (91.67%), and pus discharge (48.33%). Group A streptococcus was the most common organism isolated in both monomicrobial (53.85%) and polymicrobial (63.83%) cultures. Diabetes was the most common co morbidity observed. Fasciotomy and debridement were the mainstay of treatment with amputation rate of 23.33% and a mortality of 25%. Conclusions: Timely surgical intervention in the form of fasciotomy and debridement along with correction of malnutrition and anemia can be crucial in saving lives and limbs.